Determining guests' willingness to pay for hotel room attributes with a discrete choice model. (August 2015) - Masiero, Lorenzo; Yoonjoung Heo, Cindy; Pan, Bing
Abstract: Hotel managers need to understand the marginal utility customers associate with a specific attribute of a hotel in order to effectively set up rate fences and to price their rooms accordingly. This study adopted a stated choice experiment and discrete choice modeling method to obtain hotel guests' willingness to pay (WTP) for a specific set of room attributes within a single hotel property. The attributes include room views, hotel floor, club access, free mini-bar items, smartphone service, and cancellation policy. The study discovered that leisure travelers versus business travelers, and first-time visitors versus repeat visitors, perceive different WTP values for various attributes. These findings provide valuable information for hotel managers to segment their market and conduct revenue management practices in order to maximize revenue and profit. The results also demonstrate the value of discrete choice modeling in obtaining WTP for hotel room attributes.